IMPLEMENTATION OF PROBLEM-BASED SCIENCE LEARNING ON GAUGING STUDENTS’ LEARNING INDEPENDENT SKILL - Erika Salsabila Zahro'; Devita Sulistiana Sulistiana; Desi Anindia Rosyida (JURNAL PENA SAINS, 2025)
This study aims to determine the implementation of problem-based science learning on the learning independence of fourth-grade students and for student learning independence after the implementation of problem-based science learning. This study used a descriptive qualitative method, with the research subjects being fourth-grade teachers, the principal, and fourth-grade students consisting of 19 students. The research data were generated from interviews, observations, questionnaires, documentation, and were analyzed using the Miles and Huberman analysis model. The results showed that the implementation of problem-based science learning in grade 4 students of SDN Tembalang runs effectively. This is based on the results of observations of teacher activities getting a percentage of 96.87% and student activities getting a percentage of 92.5%. Student independence after the implementation of the problem-based science learning method shows very independent criteria with a percentage of 86% of students being responsible, 75% being active and creative in learning, 78% being able to solve learning problems, and 61% being continuous in learning. This is in accordance with the questionnaire data that shows the percentage of each learning aspect, including the responsibility aspect getting a percentage of 91.75%, active involvement in learning 92.98%, problem-solving ability 89.82%, and learning continuity, 92.98%.